Anaemia in systemic lupus erythematosus: aetiological profile and the role of erythropoietin. Issue 3 (1st March 2000) - Voulgarelis, Michalis; Kokori, Styliani I G; Ioannidis, John P A; Tzioufas, Athanasios G; Kyriaki, Despina; Moutsopoulos, Haralampos M
Abstract : OBJECTIVE: To study the prevalence of different causes of anaemia in patients with systemic lupus erythematosus (SLE) and their associations with immunological and clinical parameters and to evaluate the contribution of erythropoietin (Epo) and anti-erythropoietin (anti-Epo) autoantibodies to the development of SLE anaemia. METHODS: 132 SLE patients with anaemia (defined as haemoglobin of 12 g/dl or less for women and 13.5 g/dl or less for men) from among a total of 345 consecutive SLE patients were prospectively enrolled into the study. Standard haematological and immunological tests were performed and serum Epo and anti-Epo antibodies were assayed. RESULTS: The identified causes were anaemia of chronic disease (ACD) n=49 (37.1%), iron deficiency anaemia (IDA) n=47 (35.6%), autoimmune haemolytic anaemia (AHA) n=19 (14.4%) and other causes n=17 (12.9%). There was significant heterogeneity in the severity of anaemia between the four groups (p<0.01) with AHA cases being on average more severe. The proportion of patients with anticardiolipin antibodies, low complement levels and anti-dsDNA differed significantly among the four groups; these markers were particularly common in patients with AHA, and uncommon in patients with IDA. Twenty one of 100 tested patients had anti-Epo antibodies. Such antibodies were seen practically only in patients with ACD (odds ratio 3.1, p=0.041) and in patients with high lupus activity (ECLAM) scores (odds ratio 1.27 per point, p=0.055). Epo response was inadequate in 42.4% and 41.2% of patients with ACD and AHA, respectively. CONCLUSIONS: Anaemia in SLE usually takes the form of ACD and IDA, however autoimmune haemolysis is not uncommon. SLE patients with different causes of anaemia differ in regard to several immunological parameters. Epo response is blunted in anaemic SLE patients, particularly those with ACD and AHA.